1986
DOI: 10.1161/01.str.17.4.744
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline: cerebral blood flow and glucose utilization in conscious spontaneously hypertensive rats.

Abstract: Pentoxifylline, 0.30 mg/kg/min, significantly reduced cerebral blood flow by 10-44% in 19 of 23 regions studied in conscious spontaneously hypertensive rats. Bilateral ligation of the common carotid arteries reduced cerebral blood flow to 24-46% of resting values in 20 structures; a further reduction to 10-27% of resting values was seen after pentoxifylline in 10 cortical or subcortical structures. Thus, in conscious hypertensive rats, there is no evidence that pentoxifylline redistributes blood flow from norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Johansson 18 reported glucose utilization rates in 22-week-old SHR that resemble our results for 26-30-week-old SHR. Relative to the data in Table 2, the values of LCGU for 22-week-old SHR reported by Johansson were slightly but not significantly greater for the inferior colliculus, approximately equal for the hippocampus, and slightly but not significantly less in 11 other areas (uncorrected t tests).…”
Section: Comparisons Of Local Cerebral Glucose Utilization Findings Isupporting
confidence: 87%
“…Johansson 18 reported glucose utilization rates in 22-week-old SHR that resemble our results for 26-30-week-old SHR. Relative to the data in Table 2, the values of LCGU for 22-week-old SHR reported by Johansson were slightly but not significantly greater for the inferior colliculus, approximately equal for the hippocampus, and slightly but not significantly less in 11 other areas (uncorrected t tests).…”
Section: Comparisons Of Local Cerebral Glucose Utilization Findings Isupporting
confidence: 87%
“…The other study of intravenous oxpentifylline to report an increase in CBF used a similar method of measuring CBF to the current study, but the trial was uncontrolled and oxpentifylline was given with other medication, leading to uncertainty about the conclusions (Gabaschwili et al, 1979). In contrast to previous human studies, the results of the current study are more consistent with two carefully controlled animal studies which showed that acute administration of oxpentifylline did not alter CBF in the anaesthetised dog (Steen et al, 1981) and reduced CBF in hypertensive rats (Johansson, 1986).…”
Section: Discussionsupporting
confidence: 71%
“…in the pathogenesis of focal cerebral ischemia is unknown. The lack of a beneficial hemodynamic effect of PTX on experimental cerebral ischemia 38 - 39 and the recent observation of the lack of efficacy of hemodilution in acute ischemic stroke in community hospitals 40 raise questions about the therapeutic potential of hemorheologic modification in ischemic stroke. Additional experimental and clinical studies are needed to define further the potential efficacy of hemorheologic therapeutics in acute cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%